2023
DOI: 10.1002/ps.7628
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory behavioral responses of two Drosophila species and their pupal parasitoid to volatiles from bananas

Abstract: BackgroundBehavior‐based manipulation is an essential part of Drosophila integrated pest management (IPM). Effective compounds are useful for improving the efficiency of baits and the development of attract‐and‐kill or push–pull strategies to manage Drosophila populations. Here, we investigated the olfactory behavior of two Drosophila species, as well as their pupal parasitoid, to volatiles from bananas, for the identification of effective compounds to control fly populations.ResultsThe results showed that ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Maize weevil prefers maize while rice weevil prefers wheat if choices are available. It has been long known that insects use chemical cues to locate food sources and mates [16,[30][31][32][33]. Volatiles from hosts and the chemosensory system in insects are crucial in plant-insect interactions [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Maize weevil prefers maize while rice weevil prefers wheat if choices are available. It has been long known that insects use chemical cues to locate food sources and mates [16,[30][31][32][33]. Volatiles from hosts and the chemosensory system in insects are crucial in plant-insect interactions [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Isoamyl acetate is the main organic compound in the volatile compounds of W. anomalus , accounting for 40.4%. It has been found that isoamyl acetate is one of the volatile metabolites of some fruits and vegetables, such as bananas [ 21 ], peaches [ 22 ], yeast (ascomycetes yeasts [ 23 ]), and bacillus, and isoamyl acetate has been confirmed to have antibacterial activity. The isoamyl acetate was the primary volatile substance in Bacillus subtilis Y8, and isoamyl acetate inhibited the germination of conidia of Curvularia lunata and increased the accumulation of reactive oxygen species in pathogenic bacteria [ 24 ].…”
Section: Discussionmentioning
confidence: 99%